Analgesic and Anti-Inflammatory Effects of Ethanol Leaf Extract of Guiera Senegalensis in Murine Models - Hassan, Umar Abdulkadir; Tahir, Jalilah Ibrahim; Akanji, Comfort Foluwake; Adamu, Abdulmutalib; Tahir, Albashir (Sciences of Phytochemistry, 2025)
Pain and inflammation are global public health challenges, often requiring safer and more effective treatments. Medicinal plants like Guiera senegalensis have been traditionally used for pain and inflammatory conditions, but scientific validation of their therapeutic potential is limited. This study aimed to evaluate the analgesic and anti-inflammatory properties of ethanol leaf extract of G. senegalensis in murine models. Fresh G. senegalensis leaves were collected, authenticated, and subjected to ethanol extraction. Phytochemical analysis was conducted to identify bioactive compounds. Acute toxicity studies were performed following OECD guidelines. Analgesic effects were evaluated using the acetic acid-induced writhing test and the hot plate test, while the anti-inflammatory activity was assessed using the formalin-induced paw edema model. Phytochemical analysis revealed the presence of tannins, saponins, and flavonoids. Acute toxicity tests showed no mortality or severe adverse effects at 2000 mg/kg. The extract demonstrated dose-dependent analgesic activity, with 84% inhibition of writhing at doses of 25 mg/kg and 50 mg/kg, outperforming Diclofenac (59%). In the hot plate test, moderate central analgesic effects were observed. Anti-inflammatory tests showed significant reductions in paw edema at doses of 12.5 and 25 mg/kg, comparable to Diclofenac. Ethanol leaf extract of G. senegalensis exhibits significant analgesic and anti-inflammatory activities, likely mediated by its flavonoid, saponin, and tannin content. These findings support its traditional use and highlight its potential as a natural alternative for managing pain and inflammation.